Psychological distress does not predict decisional regret in patients undergoing spinal reconstruction for adult spinal deformity - Jesse Shen; Philip Louie; Takeshi Fujii; Caroline E. Drolet; Aiyush Bansal; Venu Nemani; Jean-Christophe Leveque; Rajiv Sethi (BMC Musculoskeletal Disorders)
Abstract Purpose The study aimed to assess the link between preoperative psychological distress and postoperative decisional regret in adult spinal deformity (ASD) surgery patients. We hypothesized that greater pre-surgery distress would correlate with higher post-surgery regret. This evaluation was based on a retrospective case series from an institution with standardized surgical guidelines for ASD. Methods This IRB-approved retrospective study analyzed our institution’s ASD database from 2014 to 2020. Eligible patients had a minimum two-year post-op follow-up and preoperative psychological distress assessment. Patients were grouped based on psychological distress levels: green, yellow, and yellow minus. Regret post-surgery was assessed using the Decision Regret Scale and SRS-22 Question 22. Logistic regression evaluated the impact of distress levels on regret, controlling for age and sex. Results Out of 167 eligible patients, 112 responded and were analyzed. No significant demographic differences were observed between responders and non-responders. Using the Decision Regret Scale, 41% expressed no regret, while 63% expressed no regret with the SRS-22 questionnaire’s Single-Item scale. Only the yellow minus group showed significant regret difference based on osteotomy, with non-recipients more likely to express regret. Conclusion This study found no significant link between psychological distress and post-operative regret in adult spinal deformity surgery after a minimum 2-year follow-up. Although nearly 60% exhibited some post-surgery regret, predicting regret based on psychological burden or demographics remains challenging. Further research is essential to identify factors contributing to post-operative regret in spinal deformity surgery patients.